Factors determining sensitivity or resistance of tumor cell lines towards artesunate - Sertel, Serkan; Eichhorn, Tolga; Sieber, Sebastian; Sauer, Alexandra; Weiß, Johanna; Plinkert, Peter K.; Efferth, Thomas (Chemico-biological interactions, 2010)
Clinical oncology is still challenged by the development of drug resistance of tumors that result in poor prognosis for patients. There is an urgent necessity to understand the molecular mechanisms of resistance and to develop novel therapy strategies. Artesunate (ART) is an anti-malarial drug, which also exerts profound cytotoxic activity towards cancer cells. We first applied a gene-hunting approach using cluster and COMPARE analyses of microarray-based transcriptome-wide mRNA expression profiles. Among the genes identified by this approach were genes from diverse functional groups such as structural constituents of ribosomes (RPL6, RPL7, RPS12, RPS15A), kinases (CABC1, CCT2, RPL41), transcriptional and translational regulators (SFRS2, TUFM, ZBTB4), signal transducers (FLNA), control of cell growth and proliferation (RPS6), angiogenesis promoting factors (ITGB1), and others (SLC25A19, NCKAP1, BST1, DBH, FZD7, NACA, MTHFD2). Furthermore, we applied a candidate gene approach and tested the role of resistance mechanisms towards established anti-cancer drugs for ART resistance. By using transfected or knockout cell models we found that the tumor suppressor p16INK4A and the anti-oxidant protein, catalase, conferred resistance towards ART, while the oncogene HPV-E6 conferred sensitivity towards ART. The tumor suppressor p53 and its downstream protein, p21, as well as the anti-oxidant manganese-dependent superoxide dismutase did not affect cellular response to ART. In conclusion, our pharmacogenomic approach revealed that response of tumor cells towards ART is multi-factorial and is determined by gene expression associated with either ART sensitivity or resistance. At least some of the functional groups of genes (e.g. angiogenesis promoting factors, cell growth and proliferation-associated genes signal transducers and kinases) are also implicated in clinical responsiveness of tumors towards chemotherapy. It merits further investigation, whether ART is responsive in clinically refractory tumors and whether the genes identified in the present study also determine clinical responsiveness towards ART.